Application of projection-based interpolation algorithm for non-stationary problem - Woźniak, Maciej; Paszyński, Maciej (Computer Science, 2016)
In this paper we present a solver for non-stationary problems using L2 projection and h-adaptations. The solver utilizes the Euler time integration scheme for time evolution mixed with the projection based interpolation techniques for solving the L2 projections problem at every time step. The solver is tested on the model problem of the heat transfer in L-shape domain. We show that our solver delivers linear computational cost at every time step.